The conditional effect of fintech on the linkage between financial inclusion and capital market development - Noah Keya Otinga; Pat Obi; Freshia Mugo-Waweru (Cogent Economics & Finance)
This study investigates the role of fintech in enhancing the relationship between financial inclusion and capital market development (CMD) across the African continent. Using static and dynamic panel estimation models, we assess how fintech can expand access to wealth-building financial products. Two measures of financial inclusion were used: financial inclusion usage (FIU) and financial inclusion access (FIA). Results show that FIU has a positive impact on CMD, while FIA has a negative effect. Fintech is found to partially mediate the relationship, in that while both measures of financial inclusion remain statistically significant, their individual effects on CMD are reduced when fintech is introduced into the model. Fintech also serves as a positive moderator, reinforcing the benefits of financial inclusion, particularly in countries with higher levels of inclusion. The study further finds that historical conditions have a greater influence than current events in shaping the growth of capital markets. We offer policy recommendations along those lines.